The Effects of Processing Parameter On Tensile Strength & Impact On Dissimilar Material Welding Between AH36 Steel & Stainless Steel 304 - Josua Hamonangan Sudibyo; Arif Wahjudi (JIPOWER : Journal of Intellectual Power, 2025)
A Merger of different type of steel are one of the very important aspects in today’s modern industrial era. One of merged steel applications that are often used are in cargo tanks used in tanker ships that carried corrosive chemical liquid. AH36 steel & stainless steel are one of the types that are used on chemical tanker construction. On dissimilar metal welding, a lot problem occurs because of not completed formed or not completed smelting of the filler metal. On this thesis, factors that may affects the final welding of these 2 different steels which is electrode type, welding current and welding voltage will be analyzed closely. Next step, specimens of welded steel were analyzed using tensile strength test, impact test & hardness checking on the optimum condition. Afterwards, optimization was conducted using Grey Relational Analysis (GRA) and Taguchi to find out types and level of factors that produce optimum results of impact & tensile strength. From the optimalization results, it can be concluded that factors which have a significant influence on the welding are electrode type and welding current. Levels that give optimum results are E7016L electrode, 85 A welding current and 110V welding voltage that gives tensile strength result of 97.781 kg.f and impact result of 75.679 j. The Results of Vickers hardness testing shows that the biggest value occurs on the root welding which is 415 HV and the smallest occurs on the AH36 base metal which is 145 HV.